CONDITIONAL RELEASE (PAROLE) IN THE SYSTEM OF EXECUTION OF SANCTIONS IN THE REPUBLIC OF MACEDONIA: IS IT IN ACCORDANCE WITH THE RECOMMENDATION REC (2003) 22 ON CONDITIONAL RELEASE (PAROLE)? - Gruevska Drakulevski, Aleksandra (Iustinianus Primus Law Review, 2012)
The author considers the Macedonian legal regime on conditional release and compares it with the principles of the Recommendation Rec(2003)22 on conditional release (parole) and the Appendix to Recommendation Rec(2003)22. The author argues that the Macedonian parole system needs certain improvements, especially regarding procedural safeguards in the decision-making process. In a separate chapter, the author of the paper analyses the data on the requests and proposals submitted by the directors of penitentiary institutions for conditional release and their acceptance and refusals in the Republic of Macedonia. According to the data on application of the conditional release (parole) in our penitentiary practice, the author concludes that it is very rarely imposed. In cases where the request is accepted, the parole is usually granted to prisoners sentenced to short sentences and it is mostly approved for up to 3 months. Hence, it turns out that the main objective of the institute conditional release is not realized. This main objective is to motivate inmates to engage actively in their own re-socialization process, to stimulate exemplary behaviour and to participate actively in the work engagement in the institution. The data prove that conditional release should be monitored and studied further in terms of its application for special categories of inmates and types of crimes. The study should facilitate setting criteria ensuring wider application of this institute.
Keywords: conditional release, parole, prison sentence, principles, procedural safeguards, revocation, re-offending